Gerakan Revivalis Islam Dan Pembentukan Negara Pakistan Prespektif Ideologi Dan Identitas Nasional - Surya Adi Nugraha; Winda Zahirotus Sa’idah; Dafa Rizqi Ramadhani; Muhammad Ichsanul Irsyad; Umar Al Faruq (CV. ITTC INDONESIA, 2024)
This abstract discusses the close relationship between the Islamic Revivalist Movement and the formation of Pakistan. The focus of this journal is on the influence of the ideology and national identity shaped by this movement on Pakistan's independence process. The journal analyzes how the